Uncaria Gambir As Natural Corrosion Inhibitor For Mild Steel In Acidic Solution - Hussin, Mohd. Hazwan (2010)
Uncaria gambir, a native Southeast Asia herbal plant has been characterized and studied as a mild steel corrosion inhibitor in acidic media. It was revealed that ethyl acetate gambir extract gave the highest condensed tannin, phenol and flavonoid content compared with other solvent extracts. Quantification studies by means of HPLC have shown that more than 80 % (wt) of gambir extract consists mainly of catechin. The effect of both ethyl acetate gambir extract and (+)-catechin hydrate as corrosion inhibitors for mild steel in 1 M HCl solution was done using various techniques such as weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements.